Geochronometria Journal on Methods and Applications of Absolute Chronology - Pazdur, Anna.; SpringerLink (Online service) (Warsaw : Versita : Imprint: Versita, co-published with Springer.)
Geochronometria is aimed at integrating scientists developing different methods of absolute chronology and using them in different fields of earth and other natural sciences and archaeology. The methods in use are physical (e.g. radiocarbon and other isotopic methods, luminescence etc.) as well as non-physical (e.g. dendrochronology or varve chronology), and they are used in such diverse fields of science as geology, palaeoclimatology, palaeobiology, palaeohydrology and archaeology.
Keywords: Earth sciences; Geology -- Statistical methods; Environmental monitoring; Quantitative Geology; Monitoring/Environmental Analysis; Earth Sciences, general